Assessing Informal Trails Impacts and Fragmentation Effects on Protected Areas using Volunteered Geographic Information - Monteiro, Luís Carlos Neto (2022)
Monteiro, L., & Cabral, P. (2022). Assessing Informal Trails Impacts and Fragmentation Effects on Protected Areas using Volunteered Geographic Information. In C. Grueau, & L. Ragia (Eds.), Proceedings of the 8th International Conference on Geographical Information Systems Theory, Applications and Management: GISTAM 2022 (Vol. I, pp. 48-55). SciTePress - Science and Technology Publications. https://doi.org/10.5220/0011088700003185